Emergency Spatiotemporal Shift: The Response of Protein Kinase D to Stress Signals in the Cardiovascular System - Wood, Brent M.; Bossuyt, Julie (Frontiers in Pharmacology, 2017)
Protein Kinase D isoforms (PKD 1-3) are key mediators of neurohormonal, oxidative, and metabolic stress signals. PKDs impact a wide variety of signaling pathways and cellular functions including actin dynamics, vesicle trafficking, cell motility, survival, contractility, energy substrate utilization and gene transcription. PKD activity is also increasingly linked to cancer, immune regulation, pain modulation, memory, angiogenesis, and cardiovascular disease. This increasing complexity and diversity of PKD function, highlights the importance of tight spatiotemporal control of the kinase via protein-protein interactions, post-translational modifications or targeting via scaffolding proteins. In this review we focus on the spatiotemporal regulation and effects of PKD signaling in response to neurohormonal, oxidant and metabolic signals that have implications for myocardial disease. Precise targeting of these mechanisms will be crucial in the design of PKD-based therapeutic strategies.